Improvement of Acoustic Properties of Alder and Soft Maple Modified with Wood Rot Fungi - Min-ji Kim; Suk-Yun Jang; Kug-Bo Shim; Chul-Ki Kim; Su-Yeon Lee (BioResources)
Wood has been used as the primary material for musical instruments for a long time. The density and elastic modulus of wood are known to be important factors in determining its acoustic properties of stringed instruments. The objective of this study was to show that fungal decay processes can be applied to improve the acoustic quality of the woods. The effects of biological modification of two woods, alder and soft maple, which were treated with wood rot fungi, were evaluated in terms of density (r), dynamic modulus of elasticity along the wood grain (EL), acoustic constant (A), and acoustic conversion efficiency (ACE). Incubation of two woods in eight species of wood rot fungi was carried out for 4 weeks. Among the fungi, Trametes versicolor and Ceriporia lacerata significantly increases the A (33.0% and 21.0%, respectively) and ACE (50.4% and 37.6%, respectively) values of alder woods. These two strains also increased the A (51.4% and 29.1%, respectively) and ACE (42.4% and 35.3%, respectively) values of soft maple. This study showed that fungal treatment significantly altered the density and elastic modulus of wood, which ultimately influenced the factor A value and the ACE value, both of which determine sound quality.